Detection of mite infested saffron plants using aerial imaging and machine learning classifier - Hossein Sahabi; Jalal Baradaran-Motie (Spanish Journal of Agricultural Research)
Aim of study: To evaluate and develop a machine learning code that uses aerial images in visible and near infrared (NIR) spectra to detect mite-infested Saffron (Crocus sativus L.) plants through processing the spectral indices to classify healthy and diseased plants. This leads to the identification of the concentration points of the bulb mites and the estimation of the percentage of infestation in the field.